The effect of irradiation on the susceptibility of Rhipicephalus appendiculatus ticks to Theileria parva infection - Young, A.S.; Leitch, L.; Irvin, A.D.; Dobbelaere, D.A.E. (Cambridge University Press, 1981)
Irradiation doses of 800 rad. or less had no detectable effect on the subsequent development of unfed nymphal Rhipicephalus appendiculatus ticks. Doses of 1600 rad. or above impaired feeding and moulting and delayed the subsequent development of unfed nymphs. At 6400 rad. no ticks completed their moult. Unfed nymphal R. appendiculatus irradiated at 0, 400, 800 and 1600 rad. were applied to 3 cattle infected with T. parva (Kiambu 4). The Theileria infections in the salivary glands of the resultant adult ticks were assessed and it was found that irradiation doses of 800 rad. or less had little effect on the Theileria infections, but an–irradiation dose of 1600 rad. greatly reduced the level of infection. The numbers of salivary gland acini in ticks of this group were reduced but the percentage of infected acini was similar.